A Comprehensive Exploration of Effective Learning Strategies Through Engaging and Interactive Kahoot Games in Educational Setting - Saputri, Zulfani Indah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
With the rapid technological advancements of the Industrial Revolution 4.0, the integration of game-based learning platforms in education has emerged as an innovative strategy to enhance student involvement and learning experiences. This article provides a comprehensive exploration of the effectiveness of Kahoot, a popular online gamification tool, as a learning strategy across various educational settings. Through a systematic review of existing literature and empirical studies, we examine the impact of Kahoot on student engagement, knowledge retention, and overall academic performance. The methodology combines qualitative and quantitative approaches, including surveys and questionnaires administered to students using Kahoot, to gather insights into their learning motivation, engagement levels, knowledge retention, and perceptions of Kahoot's effectiveness. The findings reveal that while a substantial portion of students perceive Kahoot as beneficial for improving conceptual understanding, creating a fun learning atmosphere, motivating active learning, and aiding information retention, there is also a notable diversity in preferences and responses. The article emphasizes the importance of balanced implementation and tailoring the use of educational tools like Kahoot to meet the diverse needs and learning styles of students. Ultimately, the insights presented contribute to the ongoing discourse on innovative teaching methodologies and provide educators with valuable recommendations for effectively integrating game-based learning strategies to enhance the overall learning experience.